Bulk heterojunction and inverted type solar cells using a CN-PPV derivative - Cevik, Emel; Ilicali, Derya; Egbe, Daniel Ayuk Mbi; Gunes, Serap (ELSEVIER, 2012)
We investigated the effect of solvent on the photovoltaic performance of bulk heterojunction organic solar cells comprising of an n type polymer poly (2,5-didodecyloxy-1,4-phenylene-2-cyanovinylene-2,5-dioctyloxy-1,4-phenylene-1-cyanovinylene) (DE119) and poly(3-hexylthiophene) (P3HT). We have fabricated devices from blends of P3HT and DE119 with varying acceptor ratio cast from chlorobenzene, toluene and chloroform. For the devices with 1:2 wt ratio of P3HT and DE119, respectively, cast from chlorobenzene, we achieved a short circuit current density of (J(SC)) of 0.85 mA/cm(2) and an open circuit voltage (V-OC) of 1100 mV with a FF of 0.33 leading to an efficiency of 0.3%. We also showed that inversion of the device can be accomplished using an amorphous titanium oxide (TiOx) as the hole blocking layer. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: n-type polymers; Polymer solar cells; Inverted type devices; DEVICE PHYSICS; BAND; POLYMERS; BENZOTHIADIAZOLE; SEPARATION; CONVERSION; THIOPHENE; DONOR; Energy & Fuels; Materials Science; Physics